Eye-related neoplasms in dogs: a retrospective study - Muñoz-Duque, Julián D.; Ramírez-Rojas, María C.; Duque-Arias, Santiago; Correa-Valencia, Nathalia M. (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Eye-related neoplasms in dogs have a significant impact on visual ability, comfort, and longevity. Therapeutic alternatives and prognosis vary according to type of neoplasm and its anatomical location. Objective: To describe the frequency and distribution of eye-related neoplasms affecting dogs in Aburrá valley (Antioquia province, Colombia). Methods: A retrospective collection of eye-related neoplasms in dogs, diagnosed at the Animal Pathology Laboratory of Universidad de Antioquia (Colombia), was conducted. Data spanning from years 2005 to 2017 were used. Records included age, sex, breed, neoplasm type and location, and cellular origin of neoplasm. A total of 250 eye-related-neoplasm reports affecting 246 dogs were analyzed -one report per animal, with the exception of four animals with both eyes simultaneously affected by the same type of neoplasm. Results: Animals between 8 and 11 years of age were more frequently affected by eye-related neoplasms (43.9%). Labrador retriever (19.1%), mixed-breed dogs (13.4%), and Poodle (12.2%) were the most frequently affected breeds. Neoplasms affected the eyelid in 76.8% of cases. Meibomian gland adenoma was the most frequent neoplasm (22.8%), followed by Meibomian gland epithelioma (20.0%), squamous cell carcinoma (8.8%), and melanocytoma (7.2%). The cellular origin of neoplasms [i]was epithelial in 73.6% of the cases. Conclusion: Meibomian gland adenoma was the most common eye-related neoplasm. To our knowledge, this is the first retrospective report aimed to eye-related neoplasms in dogs published in Colombia.